The association of high-sensitivity cardiac troponin I and T with echocardiographic stages of heart failure with preserved ejection fraction. (July 2019) - Hoffmann, Julia; Behnes, Michael; Ansari, Uzair; Weidner, Kathrin; Kuche, Philip; Rusnak, Jonas; Kim, Seung-Hyun; Natale, Michele; Reckord, Nadine; Lang, Siegfried; Hoffmann, Ursula; Bertsch, Thomas; et al.
Background: This study evaluates the associations between high-sensitivity troponin I and T (hs-TnI/hs-TnT) and the stages of heart failure with preserved ejection fraction (HFpEF)/diastolic dysfunction. Methods: Blood samples for biomarker measurements (hs-TnI/hs-TnT/NT-proBNP) were collected within 24 h of routine echocardiographic examination. Patients with left ventricular ejection fraction <50%, right ventricular dysfunction and moderate-to-severe valvular heart disease were excluded. Graduation of diastolic dysfunction was determined according to current guidelines. Results: A total of 70 patients were included. Hs-TnT concentrations increased significantly according to the progression of diastolic dysfunction ( P  = 0.024). Hs-TnT was able to discriminate patients with diastolic dysfunction grade III (AUC = 0.737; P  = 0.013), while NT-proBNP revealed a greater AUC (AUC 0.798; P  = 0.002). Concentrations of hs-TnI increased only numerically according to the increasing stages of diastolic dysfunction ( P  = 0.353). In multivariable logistic regression models, hs-TnT concentrations > 28 ng/L were associated with diastolic dysfunction grade III (OR = 4.7, P  = 0.024), even after adjusting for NT-proBNP. Conclusion: Increasing concentrations of hs-TnT may reflect the stages of diastolic dysfunction being assessed by echocardiography, whereas hs-TnI does not show any association with diastolic dysfunction.